Pengaruh Kebugaran Jasmani Terhadap Motivasi Belajar Siswa - Lopi; Rahman (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This research is based on the problems that have been found in SD Negeri 72 Pagaralam, namely the lack of physical fitness so that students seem to have no motivation to learn PJOK lessons. This is due to factors, the way teachers teach so that students do not have the enthusiasm to participate in sports activities. Does physical fitness affect student learning motivation and factors that affect student physical fitness in PJOK subjects. This research is a quantitative survey type. The population of students at SD Negeri 72 Pagaralam amounted to 326 students and the sample was 52 students in grade V. Data collection techniques were questionnaires, observation, documentation. Then analyzed using validity, reliability, normality, linearity and hypothesis testing, simple linear regression tests. The results obtained through the hypothesis test were seen as significant 0.000 <0.05 then Ha was accepted and Ho was rejected. So there is an influence of physical fitness on student learning motivation in PJOK subjects. The factors that affect students' physical fitness are the first factor from within the student, namely: gender, physical health, interest in learning. Second, school environmental factors, namely: warming up, the way teachers teach, peers, exercise habits.